2021
DOI: 10.3390/cancers13235971
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Barrett’s Esophagus Cell Lines Resemble Esophageal Squamous Cell Carcinoma Instead of Esophageal Adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) is strongly associated with Barrett’s esophagus (BE), a pre-malignant condition resulting from gastric reflux. Esophageal squamous cell carcinoma (ESCC), the other major subtype of esophageal cancer, shows strong association with smoking and alcohol intake and no association with gastric reflux. In this study, we constructed and validated gene expression signatures of EAC vs. ESCC tumors using publicly available datasets, and subsequently assessed the enrichment levels of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This is in accordance with Panda et al, who constructed and validated gene expression signatures of EAC vs. ESCC tumors using publicly available datasets. They observed that OE33 clusters are close to primary EAC tumors, while OE19 could be either classified as an EAC or ESCC cell line [ 80 ]. To sum up, differences in gene expression patterns require careful evaluation to enable the selection of appropriate in vitro tools for future BE and EAC studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with Panda et al, who constructed and validated gene expression signatures of EAC vs. ESCC tumors using publicly available datasets. They observed that OE33 clusters are close to primary EAC tumors, while OE19 could be either classified as an EAC or ESCC cell line [ 80 ]. To sum up, differences in gene expression patterns require careful evaluation to enable the selection of appropriate in vitro tools for future BE and EAC studies.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, differences in gene expression patterns require careful evaluation to enable the selection of appropriate in vitro tools for future BE and EAC studies. For instance, Tratnjek et al have attempted to standardize an EAC in vitro model for drug testing using an esophageal adenocarcinoma FLO-1 cell line in anticancer drug studies and EAC tumor biology [ 81 ]; however, according to Panda et al, this cell line may not be suitable for studying EAC tumors [ 80 ]. Furthermore, it is worth mentioning that cell cultures apparently lack a mechanical microenvironment and the proper distribution of oxygen, nutrients, and metabolic products; thus, 3D culture models are a novel option used in the research of esophageal diseases as a perspective in future research [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is the seventh most commonly diagnosed cancer (604,100 new cases) and the sixth commonest cause of cancer-related mortality (544,076 deaths) around the world in 2020 [1]. Two main EC types are known, including esophageal adenocarcinoma and esophageal squamous cell carcinoma (ESCC), which have quite distinct epidemiology and etiology [2]. ESCC, which usually originates from the lining of the esophageal squamous epithelium and occurs predominantly in the upper and mid-esophagus, is the predominant form of EC worldwide.…”
Section: Introductionmentioning
confidence: 99%